Phase II study of rucaparib and nivolumab in patients with leiomyosarcoma - Robert G Maki; Martina Bradic; Phillip Wong; William Tap; Vicky Makker; Sandra D’Angelo; Angela Green; Mrinal M Gounder; Evan Rosenbaum; Ciara M Kelly; Jason E Chan; Ping Chi; et al. (Journal for ImmunoTherapy of Cancer)
Background Objective responses to immune checkpoint inhibitors (ICI) in leiomyosarcoma (LMS) are rare. Response rates may be increased by combination with other drugs known to promote immune infiltration, such as poly(ADP-ribose) polymerase (PARP) inhibitors, which have led to benefit in BRCA-altered uterine LMS. We therefore evaluated the combination of a PARP inhibitor, rucaparib, and the anti-programmed death receptor-1 monoclonal antibody, nivolumab, in patients with advanced LMS and investigated its effects on the tumor immune microenvironment.Methods This was an open-label, single-center, single-arm, phase II study in patients with advanced refractory LMS. Full protocol available Patients were treated with rucaparib 600 mg orally, two times daily, continuously and nivolumab 480 mg intravenously on day 1 of a 28-day cycle. Re-staging scans were performed every 8 weeks. Blood and tissue samples were collected at baseline and at week 8 on treatment. The primary objective was the best objective response rate by 24 weeks using Response Evaluation Criteria in Solid Tumour (RECIST V.1.1). Secondary objectives included treatment-related toxicity, progression-free survival, overall survival, and changes in immune pathways in blood and tumor.Results 20 patients with LMS were enrolled. There was one partial response (PR) (5%) in a patient with uterine LMS and a somatic BRCA deep deletion. 19 (95%) patients had a treatment-related adverse event (TRAE) and 7 (35%) had a grade 3 or higher TRAE. Interferon (IFN) α and γ hallmark pathways were more highly expressed in patients who derived benefit from treatment (at least stable disease by 16 weeks) vs those who did not in both baseline (adjusted p=0.005 for IFN-α, 0.03 for IFN-γ) and on-treatment biopsies (adjusted p=0.0002 for IFN-α, 0.0001 for IFN-γ), but the abundance of tumor immune cell populations did not differ between these groups at either time point.Conclusion The addition of a PARP inhibitor did not improve the efficacy of ICI in LMS. Adverse events, especially due to overlapping toxicities, were frequent and often led to dose delays and modifications.